Applying population-based threshold models to quantify and improve seed quality attributes - Bradford, Kent J. (Burleigh Dodds Series in Agricultural Science, 2022)
Achieving rapid and uniform stand establishment in crops requires a combination of high-quality seeds and appropriate environmental conditions. In particular, temperature and soil moisture (or water potential) are the major factors influencing germination in the field. In this chapter, we focus on the application of population-based threshold (PBT) models to characterize seed germination time courses and how environmental and technological inputs influence them. Viewing seed quality as a product of the behavior of populations of individual seeds is critical for understanding the causes and consequences of poor performance. Quantitatively characterizing seed population features enables their use in seed sorting and seed enhancement, and provides phenotypes for use in research, breeding, conservation and restoration. We believe that PBT models are essential tools to enable full utilization of new advances in seed technology to improve seed quality and enable successful stand establishment in agriculture or in natural settings.